Influence of the N terminus on the biophysical properties and pharmacology of TREK1 potassium channels. - Veale, E; Al-Moubarak, E; Bajaria, N; Omoto, K; Cao, L; Tucker, S; Stevens, E; Mathie, A (2014)
TWIK-related K(+) 1 (TREK1) potassium channels are members of the two-pore domain potassium channel family and contribute to background potassium conductances in many cell types, where their activity can be regulated by a variety of physiologic and pharmacologic mediators. Fenamates such as FFA (flufenamic acid; 2-{[3-(trifluoromethyl)phenyl]amino}benzoic acid), MFA [mefenamic acid; 2-(2,3-dimethylphenyl)aminobenzoic acid], NFA [niflumic acid; 2-{[3-(trifluoromethyl)phenyl]amino}nicotinic acid], and diclofenac [2-(2-(2,6-dichlorophenylamino)phenyl)acetic acid] and the related experimental drug BL-1249 [(5,6,7,8-tetrahydro-naphthalen-1-yl)-[2-(1H-tetrazol-5-yl)-phenyl]-amine] enhance the activity of TREK1 currents, and we show that BL-1249 is the most potent of these compounds. Alternative translation initiation produces a shorter, N terminus truncated form of TREK1 with a much reduced open probability and a proposed increased permeability to sodium compared with the longer form. We show that both forms of TREK1 can be activated by fenamates and that a number of mutations that affect TREK1 channel gating occlude the action of fenamates but only in the longer form of TREK1. Furthermore, fenamates produce a marked enhancement of current through the shorter, truncated form of TREK1 and reveal a K(+)-selective channel, like the long form. These results provide insight into the mechanism of TREK1 channel activation by fenamates, and, given the role of TREK1 channels in pain, they suggest a novel analgesic mechanism for these compounds.